Solarium use and risk for malignant melanoma: meta-analysis and evidence-based medicine systematic review - Burgard, Barbara Louise; März, Winfried (Anticancer research, 2018)
Background: There is an ongoing debate whether solarium use (indoor tanning/artificial UV) may increase the risk for primary cutaneous malignant melanoma. Aim: A systematic literature search was conducted using MEDLINE and ISI Web of Science. Included studies were critically assessed regarding their risk of bias, and methodological shortcomings. Levels of evidence and grades of recommendation were determined according to guidelines of the Oxford Centre for Evidence-Based Medicine. Summary risk estimates and 95% confidence intervals for four different outcomes (ever exposure, exposure at younger age, high/low exposure vs. non-exposure) were derived from random-effects meta-analyses to account for possible heterogeneity across studies. Results: Two cohort and twenty-nine case-control studies were eligible. Overall, quality of included studies was poor as a result of severe limitations, including possible recall and selection bias, and due to lack of interventional trials. Summary risk estimates suggested a weak association (odds ratio (OR)=1.19, 95% confidence interval (CI)=1.04-1.35, p=0.009) for ever-exposure to UV radiation from a solarium with melanoma risk. However, sensitivity analyses did not show an association for studies from Europe (OR=1.10; 95%CI=0.95-1.27, p=0.218), studies with low risk of bias (OR=1.15; 95%CI=0.94-1.41, p=0.179), and studies conducted after 1990 (OR 1.09; 95%CI=0.93-1.29, p=0.295). Moreover, moderate associations were found for first exposure to UV radiation from a solarium at younger age (<25 years) and high exposure (>10 sessions in lifetime) with melanoma risk. However, for all outcomes analyzed, overall study quality and resulting levels of evidence (3a-) and grades of recommendation (D) were low due to lack of interventional studies and severe limitations including unobserved or unrecorded confounding. Conclusion: Current scientific knowledge is mainly based on observational studies with poor quality data, which report associations but do not prove causality. At present, there is no convincing evidence that moderate/responsible solarium use increases melanoma risk.